The Impact of Female Executives on the Quality and Comparability of Financial Statements: Evidence from the U.S. - Xiang (Gail) Gao; Emmanuel Sequeira; Qifeng (Charles) Wu (Copernican Journal of Finance & Accounting)
In this article, we examine the impact of female CFOs on Financial Statement Comparability (FSC) in a U.S. setting. Using a sample of publicly traded U.S. firms between the years 1992 and 2023, we compare firms with female CFOs against those with male CFOs using pooled panel regressions. We also examine firms with male to female CFO changes and vice versa using difference in difference regressions. We find that female CFO firms have a 1.1% higher FSC on average than male CFO firms. Further, firms that switch from having a male CFO to a female CFO experience FSC increases of 17.5%. On the contrary, firms that switch from having female CFOs to male CFOs experience FSC decreases of 7.6%. Thus, we conclude that firms with female CFOs have higher FSC than those with male CFOs. We believe that our findings are significant to regulators and legislators and also add supporting evidence in favor of the push for increased female representation in the C-suite.